The Waste Sorting Education Media: An Innovation with Android-based Game - Purnaningtyas, Afiani; Harsono; Fuadi, Djalal; Muhibbin, Ahmad (Jurnal Penelitian dan Pengembangan Pendidikan, 2023)
Knowledge of waste classification and segregation is very important considering that currently Indonesia is one of the largest plastic waste contributor countries in the world. Games that can be modified for educational purposes are educational games, especially in waste sorting. This study aims to develop an android-based waste sorting educational game (with the types of waste that appear in the school environment), as well as how to sort this android-based waste. Educational games are very appropriate as educational or learning media. Researchers use a research and development design or Research and Development Design (R&D) with the Borg and Gall model. In this initial study, it was carried out up to the small-scale user trial stage. The collection of teacher response data as a media user is carried out using an application usability instrument, namely the System Usability Scale (SUS). The research was conducted in 4 elementary schools. The educational game Sorting Trash was developed using Construct 3, Canva and Pixlr. This game is operated with an Android-based smart phone so that it is easily accessible to the wider community. The results of the validity test by media experts and material experts show that the results of the Android-based Sort Waste educational game are very valid, so they are very suitable for use as educational media for elementary school students.